Refining Professional Development For Science Teachers In Early Childhood Education - Forkpah, Eric (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa Tanah Datar Sumatera Barat, 2024)
This research aims to address the imperative need for refining professional development opportunities for Teacher in science in early childhood education (ECE)in Bong County, Liberia. Employing a grounded theory approach, the study seeks to unravel the complexities of the current professional development landscape and formulate context-specific strategies to refine the quality of education for young learners. Through qualitative data collection methods, including interviews, focus groups, and observations, the research aims to develop a grounded theory that can inform policy and practice in fostering the continuous growth and effectiveness of ECE educators in the region.Keywords: Fire outbreaks, causes, consequences, Monrovia, Liberia